The driving force governing room temperature grain coarsening in thin gold films. (15th March 2017) - Glushko, O.; Cordill, M.J.
Abstract: Strong room-temperature grain coarsening in gold films on polyimide induced by cyclic uniaxial mechanical strain is demonstrated. Detailed electron backscatter diffraction analysis revealed that, in contrast to the predictions of shear-coupled grain boundary migration model, the grain coarsening is isotropic and coarsened grains do not exhibit any specific crystallographic orientations or misorientations to the neighboring grains. It is shown that a thermodynamic model where the driving force appears due to the difference in yield stresses between the grains with different sizes provides an adequate explanation of the experimental data. Graphical abstract: